We have to prove : cos x + cos 2x + cos 3x = cos 2x(1 + 2cos x)

We know that cos A + cos B = 2 * cos (A + B)/2 * cos (A − B)/2

Now cos x + cos 2x + cos 3x

=> 2 * cos (4x / 2) * cos (2x / 2) + cos 2x

=> 2 cos 2x * cos x + cos 2x

=> cos 2x ( 1 + 2 cos x)

Therefore we prove that

**cos x + cos 2x + cos 3x = cos 2x(1 + 2cos x)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now